Validity of ordination questioned Canon 10 - Huels, John M. 1950- (2006)
At a recent ordination of a deacon, the bishop inadvertently neglected to impose hands on the candidate until after he had said the prayer of ordination. Afterwards, the deacon questioned whether he was validly ordained. The bishop, to remove all doubts, conditionally ordained him privately by imposing hands and saying the prayer of ordination again. Is it necessary, for validity, that the imposition of hands precede the prayer of ordination? If so, did the bishop validly ordain by the imposition of hands and prayer of ordination alone, without observing anything else in the rite?
Keywords: Katholische Kirche; Weihe; Gültigkeit; Diakon; Sakramentenrecht